ESTADO Y PERCEPCIÓN DE LOS SERVICIOS ECOSISTÉMICOS DE LAS RIBERAS DEL MATANZA-RIACHUELO - Faggi, Ana; Breuste, Jürgen; Melignani, Eliana; Johnson, Barbara Guida (European Scientific Journal, ESJ, 2015)
Cities grow continuously and thereby environmental conditions deteriorate especially through pollution. The urban nature - urban green - becomes relevant considering its ecological, economic, and social functions which contributes significantly to the compensation and mitigation of environmental burdens. Through the application of indexes and interviews, we analyse the river banks in the Matanza Riachuelo watershed through an environmental perspective and the perception of residents. The results confirms that riparian areas are multidimensional. While riverbanks diminish their environmental quality along an urban to rural gradient, the environmental perception is more complex. Gender and the proximity of residents to the riparian edge influenced opinions and attitudes in the three sectors of the watershed.